Single amino acid residue as a functional determinant of rod and cone visual pigments - Imai, Hiroo (The National Academy of Sciences of the USA, 1997)
The visual transduction processes in rod and cone photoreceptor cells begin with photon absorption by the different types of visual pigments. Cone visual pigments exhibit faster regeneration from 11-cis-retinal and opsin and faster decay of physiologically active intermediate (meta II) than does the rod visual pigment, rhodopsin, as expected, due to the functional difference between rod and cone photoreceptor cells. To identify the amino acid residue(s) responsible for the difference in molecular properties between rod and cone visual pigments, we selected three amino acid positions (64, 122, and 150), where cone visual pigments have amino acid residues electrically different from those of rhodopsin, and prepared mutants of rhodopsin and chicken green-sensitive cone visual pigment. The results showed that the replacement of Glu-122 of rhodopsin by the residue containing green- or red-sensitive cone pigment converted rhodopsin’s rates of regeneration and meta II decay into those of the respective cone pigments, whereas the introduction of Glu-122 into green-sensitive cone visual pigment changed the rates of these processes into rates similar to those of rhodopsin. Furthermore, exchange of the residue at position 122 between rhodopsin and chicken green-sensitive cone pigment interchanges their efficiencies in activating retinal G protein transducin. Thus, the amino acid residue at position 122 is a functional determinant of rod and cone visual pigments.